SARS-CoV-2 and Coronaviruses: Understanding Transmission, Impact, and Strategies for Prevention and Treatment - Seyede Nafise Tabatabaei; Zahra Keykhaee; Saghi Nooraei; Mohammad Amin Ayati; Mohammad Behzadmand; Saba Azimi; Fatemeh Eskati; Gholamreza Ahmadian (Drugs and Drug Candidates)
COVID-19, first identified in December 2019 in Wuhan, China, is caused by the SARS-CoV-2 virus, a pathogen that primarily targets the respiratory system and can lead to severe conditions such as acute respiratory distress syndrome (ARDS). Among the seven coronaviruses known to infect humans, three—SARS-CoV, MERS-CoV, and SARS-CoV-2—are associated with severe illness and significant morbidity. SARS-CoV-2 is an enveloped, single-stranded RNA virus that utilizes the angiotensin-converting enzyme 2 (ACE2) receptor for cellular entry. The genetic sequence of SARS-CoV-2 is highly mutable, leading to the emergence of variants that alter disease pathology and transmission dynamics. The World Health Organization (WHO) has classified these mutations into variants of concern (VOCs), variants of interest (VOIs), and variants under monitoring (VUMs). This review provides an in-depth analysis of both historical and emerging SARS-CoV-2 variants, summarizes recent advancements in diagnostic methods for SARS-CoV-2 detection, and discusses current therapeutic strategies for COVID-19, with a particular focus on virus-like particle (VLP) vaccines developed in recent years. Additionally, we highlight ongoing therapeutic approaches and their implications for managing COVID-19.